Mücken und Zecken als Krankheitsvektoren: der Einfluss der Klimaerwärmung - Hemmer, Christoph Josef; Emmerich, Petra; Loebermann, Micha; Frimmel, Silvius; Reisinger, Emil Christian (DMW - Deutsche Medizinische Wochenschrift, 2018)
During the last 135 years, the average temperature in Germany has increased by 1.4 °C. By 2050, a further rise by 1.5 °C is expected. This is associated with an increase of precipitation during the winter months. This climate change probably will improve both the growth conditions for mosquitoes and ticks, as well as their ability to transmit infectious diseases. Today, vectors that have not yet been present are invading into Germany. Among them is Aedes albopictus, which transmits Chikungunya, Zika, and Dengue Fever. Also, spreading of autochthonous malaria and West Nile Fever appear possible in Germany. Because of the increased presence of Phlebotomus species, leishmaniasis should be considered as a potential differential diagnosis in unclear hematologic diseases. Among the tick-borne diseases, climate change has already led to increased case numbers of Borreliosis and Tick Borne Encephalitis (TBE), and Crimean Congo Virus is spreading from the Balkan region towards Central Europe. This requires physicians to consider additional differential diagnoses in febrile illnesses.
Keywords: Klimaerwärmung; Vektorkompetenz; Mücken; Zecken; Infektionskrankheiten